Five hole probe errors caused by fluctuating incidence - Coull, J; Dickens, T; Ng, H; Serna, J (EDP Sciences, 2022)
Steady multi-hole pressure probes are used extensively in turbomachinery research. While various sources of error are known, this paper demonstrates that fluctuations in probe incidence can be particularly damaging for accuracy. A simple, quasi-steady model of five-hole-probe response explains why angle fluctuations can cause large errors in the indicated total and static pressure. The model explains why measurements in a shedding wake over-estimated loss by 40%. Simulated traverses behind rotors show similar behavior: fluctuating incidence causes efficiency to be under-estimated by over 1% in some cases. The model can correct five-hole-probe errors using an estimate of unsteady flow angles. This approach reduces errors by an order of magnitude and can be used to post-correct existing test data.